Sexual abstinence: What is the understanding and views of secondary school learners in a semi-rural area of North West Province, South Africa? - Kebogile Mokwena; Mamaponesa Morabe (Taylor & Francis Group, 2016)
Among strategies to prevent HIV, other sexually transmitted infections (STIs) and unwanted pregnancies, are programs that promote sexual abstinence among adolescents. However, literature suggests that there may be differences in the understanding of abstinence across adolescents, and this study sought to explore the understanding of sexual abstinence among both male and female learners in a secondary school in a semi-rural area of North West Province, South Africa. Focus group discussions were used to collect data from learners who were in grades 8-10 at the time of the study. The findings are that the learners in this area understand sexual abstinence as the decision not to have sex, and this was associated with prevention of HIV, STIs and unwanted pregnancies, which ensures a better future. Barriers to sexual abstinence include peer pressure, myths and wrong perceptions about sex, influence of drugs and alcohol and the influence of television. Based on how it is delivered, school-based sex education was viewed as both an enabler and barrier to sexual abstinence. It is recommended that programs to promote sexual abstinence be strengthened and such programs be community-based.